Robotic-Assisted Minimally Invasive Surgery: Communication in a Complex Socio-Technical System. - Cunningham, Stacey. (2017)
Abstract: Surgical robots are controlled from a remote console, inhibiting face-to-face communication between the surgeon and the rest of the team. This research viewed the robotic operating room as a socio-technical system where team members adapt to technology by modifying their communication. The goal of this research was to understand the nature of communication in robotic surgery. A field study was conducted to examine communication as a function of workplace culture and experience level with the robot. Surgical teams in the US and France had different workflows, roles, and communication patterns. The study revealed the difficulty of communicating spatial information during surgery. Controlled experiments were conducted to examine spatial communication in a simulated robotic surgical task. Results indicate that using a spatial communication aid may positively impact task time and communication, regardless of natural spatial ability. The research contributes to robotic surgery requirements analysis, training protocol design, and future telesurgery applications.; Thesis (M.S.)--Tufts University, 2012.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Caroline Cao.; Committee: Holly Taylor, and Jason Rife.; Keywords: Biomedical engineering, and Cognitive psychology.